2023
DOI: 10.3389/frsus.2023.1190470
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning circular economy from policy to practice in Kenya

Abstract: Policies are imperative in assessing how certain proposed actions or practices can be implemented. In the context of the circular economy, public policies have been influential in determining the way practices are adopted and implemented. In specific contexts, policies can be used to assess a country's preparedness to transition to the circular economy by examining how those that are formulated support the transition. This study examines Kenya's circular economy policy landscape by looking at the strides made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…As noted by other scholars in an African context, there is an opportunity for more proactive governance to foster circular value creation (Muriithi and Ngare, 2023). In agreement with Banda et al (2023), the findings point to opportunities to support investment interest through SIs for sector-specific tax exemptions and benefits; tariff-free imports on equipment; investment funds and other fiscal incentives; and dedicated registration codes.…”
Section: Foster Circular Innovationsupporting
confidence: 74%
See 3 more Smart Citations
“…As noted by other scholars in an African context, there is an opportunity for more proactive governance to foster circular value creation (Muriithi and Ngare, 2023). In agreement with Banda et al (2023), the findings point to opportunities to support investment interest through SIs for sector-specific tax exemptions and benefits; tariff-free imports on equipment; investment funds and other fiscal incentives; and dedicated registration codes.…”
Section: Foster Circular Innovationsupporting
confidence: 74%
“…Many CE advocates stress the importance of a multistakeholder approach for inclusive circularity (Barford and Ahmad, 2021;EMF, 2021a;Muriithi and Ngare, 2023). In agreement with suggestions in the literature (Schröder et al, 2023), the findings point to the importance of including the informal workforce in a future CE agenda.…”
Section: Embrace An Inclusive Approachsupporting
confidence: 55%
See 2 more Smart Citations
“…However, the concept is still novice in Africa (Mhlanga et al, 2022). Kenya (Muriithi and Ngare, 2023), South Africa (Republic of South Africa, 2020) and Nigeria (Olukanni et al, 2018) are among the few countries in Africa reported having policies and practices that align with CE.…”
Section: Challenges To Circular Economymentioning
confidence: 99%